The Effectiveness of Practice, Presentation-Demonstration, and Presentation-Discussion (PPDP) Learning Strategies Toward Students’ Conceptual Understanding - Kadir, Dalimawaty; Nuzalifa, Yossie Ulfa; Siregar, Nurmawati; Rhamadona, Fitria (Journal Corner of Education, Linguistics, and Literature, 2025)
Biology is one of the scientific fields that was born and developed through the steps of observation, problem formulation, making hypotheses based on experiments, drawing conclusions, and discovering concepts and theories. Biology learning will not be separated from laboratory or practical activities. Understanding the concept plays a very pivotal role in learning activities and has become the basis for achieving the learning outcomes. One of the instructional strategies is called PPD (Practice, Presentation and Discussion). This study aimed to determine the effect of the PPD strategies in enhancing students' conceptual understanding. This study applied a pre-experimental research method with One Group Pretest-Posttest Design. The subjects were twelfth grade high school students. These subjects were randomly selected with the number of 35 students. The results showed that the application of the PPD strategies has proven to be influential in enhancing students’ mastery of photosynthesis concepts. The increase in concept mastery could be viewed from the level change of students' comprehension as the mean score of 43.18, where the students’ initial knowledge (pretest) was 38.12, significantly increasing after the implementation of the PPD strategies (posttest) as of 81.30. Based on the standard of minimal accomplishment criteria, the effectiveness of the PPD strategies on students’ concept mastery was between 71-85 which was stated in the high category.